Physiologically‐based pharmacokinetic model of vaginally administered dapivirine ring and film formulations. (19th June 2018) - Kay, Katherine; Shah, Dhaval K.; Rohan, Lisa; Bies, Robert
Abstract : Aims: A physiologically‐based pharmacokinetic (PBPK) model of the vaginal space was developed with the aim of predicting concentrations in the vaginal and cervical space. These predictions can be used to optimize the probability of success of vaginally administered dapivirine (DPV) for HIV prevention. We focus on vaginal delivery using either a ring or film. Methods: A PBPK model describing the physiological structure of the vaginal tissue and fluid was defined mathematically and implemented in MATLAB. Literature reviews provided estimates for relevant physiological and physiochemical parameters. Drug concentration–time profiles were simulated in luminal fluids, vaginal tissue and plasma after administration of ring or film. Patient data were extracted from published clinical trials and used to test model predictions. Results: The DPV ring simulations tested the two dosing regimens and predicted PK profiles and area under the curve of luminal fluids (29 079 and 33 067 mg h l –1 in groups A and B, respectively) and plasma (0.177 and 0.211 mg h l –1 ) closely matched those reported (within one standard deviation). While the DPV film study reported drug concentration at only one time point per patient, our simulated profiles pass through reported concentration range. Conclusions: HIV is a major public health issue and vaginal microbicides have the potential to provide a crucial, female‐controlled option for protection. The PBPK model successfully simulated realistic representations of drug PK. It provides a reliable, inexpensive and accessible platform where potential effectiveness of new compounds and the robustness of treatment modalities for pre‐exposure prophylaxis can be evaluated.